A bad day for scandal - Littlefield, Sophie (Minotaur Books, 2011)
Blackmailed by a powerful businesswoman to help dispose of a dead body, Stella Hardesty is implicated in the woman's subsequent disappearance and travels to Kansas City for answers, only to discover a series of killings tied to a corrupt judge.